Tuning Electrical Conductance of MoS2Monolayers through Substitutional Doping - Gao, Hui; Suh, Joonki; Cao, Michael C.; Joe, Andrew Y.; Mujid, Fauzia; Lee, Kan Heng; Xie, Saien; Xie, Saien; Lee, Jae Ung; Kang, Kibum; Kim, Philip; Muller, David A.; et al. (Nano Letters, 2020)
Tuning electrical conductivity of semiconducting materials through substitutional doping is crucial for fabricating functional devices. This, however, has not been fully realized in two-dimensional (2D) materials due to the difficulty of homogeneously controlling the dopant concentrations and the lack of systematic study of the net impact of substitutional dopants separate from that of the unintentional doping from the device fabrication processes. Here, we grow wafer-scale, continuous MoS2 monolayers with tunable concentrations of Nb and Re and fabricate devices using a polymer-free approach to study the direct electrical impact of substitutional dopants in MoS2 monolayers. In particular, the electrical conductivity of Nb doped MoS2 in the absence of electrostatic gating is reproducibly tuned over 7 orders of magnitude by controlling the Nb concentration. Our study further indicates that the dopant carriers do not fully ionize in the 2D limit, unlike in their three-dimensional analogues, which is explained by weaker charge screening and impurity band conduction. Moreover, we show that the dopants are stable, which enables the doped films to be processed as independent building blocks that can be used as electrodes for functional circuitry.
Keywords: Dopant concentrations; Electrical conductance; Electrical conductivity; Impurity band conduction; Semiconducting materials; Three-dimensional analogues; Two Dimensional (2 D); Unintentional doping; Doping; impurity conduction; metal-organic chemical vapor deposition; molybdenum disulfide; two-dimensional materials